Peran Emotional Eating Terhadap Potensi Terbentuknya Perilaku Pembelian Makanan Secara Impulsif Pada Mahasiswa - Sujoko, Sujoko; Hazerin Duha, Christina Eben; Yuniati, Rosita (Universitas Muhammadiyah Jember, 2023)
Emotional eating is an eating behavior that is influenced by various kinds of negative feelings or coping responses to negative feelings such as sadness, stress, anger, anxiety, depression, and others that can trigger the potential formation of impulsive purchasing behaviors, especially food products. This is because the desire to eat to meet their emotional needs will indirectly lead individuals to make impulsive purchases. This study aims to determine the role of emotional eating on the potential formation of impulsive food buying behavior in students who are in their thesis. Research is carried out by quantitative methods. The population is 333 with the sample used is 179 thesis students for the 2021/2022 even academic year class of 2015-2018 Setia Budi Surakarta University. The sampling technique used is simple random sampling. The measuring instrument of this study used the Impulsive Buying Tendence scale and the Dutch Eating Behavior Questionnaire scale. The data analysis method used is a simple linear regression analysis. The results of data analysis show a coefficient correlation value of 0.301 with p = 0.008 (p0.05). This proves that Emotional Eating plays a positive role in the potential formation of Impulsive Food Buying Behavior, the higher the Emotional Eating, the higher the Impulsive Food Buying Behavior. So in this case the proposed hypothesis is accepted.